SELECTION AND PROFESSIONAL TRAINING OF PERSON PROFILERS IN THE STATE BORDER GUARD OF THE REPUBLIC OF LATVIA - Madžuls, Juris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The effectiveness of profiling depends directly on the professional skills of the employee – profiler.  The special attention should be paid to the selection and training of profilers.  Profiling is a matter of state, public or company security and it is not acceptable that accidental person enters the profilers’ community. The aim of the paper is to identify the possibilities of improving the profiler candidates selection system and their professional preparedness in line with current socio-economic, political and migration trends in Europe and in the world. The research was done in the State Border Guard College of the Republic of Latvia. For this purpose analysis and evaluation of documents, scientific, pedagogical and psychological literature was performed and conclusions about the necessity of profiler selection and preparedness processes development were summarized.The author brought forward conclusion that with strict selection criteria and future qualification raising possibility - the special position held – profiler, should be established.